The prognostic impact of cirrhosis on patients receiving maintenance haemodialysis. Issue 1 (14th May 2019) - Artru, Florent; Louvet, Alexandre; Glowacki, François; Bellati, Sara; Frimat, Marie; Gomis, Sebastien; Castel, Hélène; Barthelon, Justine; Lassailly, Guillaume; Dharancy, Sebastien; Noel, Christian; Hazzan, Marc; et al.
Summary: Background: Further study is needed on the prognostic impact of cirrhosis on haemodialysis patients. Aim: To evaluate cirrhosis' impact according to severity on survival and to provide therapeutic guidelines for haemodialysis cirrhotic patients. Methods: Patients with end‐stage renal failure treated with haemodialysis were included retrospectively from 01/01/2000 to 31/12/2004 and prospectively from 01/01/2005 to 31/12/2014 in our French Region. Clinical data, presence of cirrhosis and its severity were recorded at the beginning of haemodialysis. The primary endpoint was 2‐year survival. Results: Seven thousand three hundred and fifty‐four patients (96%) without cirrhosis and 304 patients (4%) with cirrhosis were included. Two‐year survival in noncirrhotic patients was higher than in cirrhotic patients (71.7% vs 54.4%, P  < 0.0001). Patients with decompensated cirrhosis had a worse 2‐year outcome (44.1%) as compared to compensated cirrhotic (62.8%, P  = 0.002) and noncirrhotic patients (71.7%, P  < 0.0001). Compensated and decompensated cirrhosis were independent predictive factors of 2‐year mortality. In sensitivity analysis restricted to cirrhotic patients, 2‐year survival of Child‐Pugh A patients was higher than in Child‐Pugh B and C patients (65.5% vs 27.7% vs 0%, P  < 0.0001). Development of predictive models based either on severity scores (MELD and Child‐Pugh) and extrahepatic comorbidities allowed correct classification of around 70% of patients in terms of mortality and may help to better stratify mortality risk in this population. Conclusions: Cirrhosis is independently associated with mortality in haemodialysis patients. Patients with severe cirrhosis have a poor 2‐year outcome. Severity of cirrhosis and presence of extrahepatic comorbidities should be considered when deciding to initiate renal replacement therapy.